تمييز عيب عدم الاختصاص بالتشريع, وعلاقته بالنص التشريعي المنظم للمبادئ العامة للديمقراطية - خضر صالح شبر رافع; نهير راهي احمد (Journal of College of Education, 2021)
Summary The Constitution, which is defined by the Constitution to enact legislation, has the right to pass legislation. No other party has that right except by authorizing the constitutional document, and when it violates the right to issue any legislation, we are in front of flawed legislative provisions. The judiciary must be overruled. As to the relationship between the flaw of legislative incompetence and the general principles of democracy, it is clear that the legislative power has passed a law governing one of the general principles of democracy and that it has exceeded its competence to regulate that democratic principle. Some constitutional provisions establish specific procedures for the enactment of a particular law in terms of the competent authority to propose it to other stages, or the legislature may pass such legislation relating to a democratic principle and be incompetent in terms of place, time or other elements. Here we have a clear relationship between the flaw of incompetence and that democratic principle, and the study is focused on explaining that relation by standing on the most important judicial decisions of the supreme and constitutional courts in both the Federal Germany and Iraq. The statement of competence to regulate the general principles of democracy is not enjoyed by the legislature through the relevant constitutional provisions and constitutional provisions